2009
DOI: 10.1080/00220380902811058
|View full text |Cite
|
Sign up to set email alerts
|

Too Many People and Too Few Livestock in West Africa? An Evaluation of Sandford's Thesis

Abstract: We examine whether Stephen Sandford's (2006b) 'too many people, too few livestock' thesis for the Greater Horn of Africa applies to West Africa. In a comparative study of seven pastoral systems across West Africa we found that pastoralists have generally successfully adapted to pressures on grazing resources. We describe three adaptive strategies: 1) integration and intensification in the Sudanian zone; 2) movement to the Sub-Humid zone; and 3) extensification in the Sahelian zone. We end by proposing four int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…The results further reveal that households who keep moving their cattle herds to better pasture had achieved higher income than those who never moved. In congruence with this finding, Moritz et al (2009) indicated that livestock mobility is the innovative means of sustaining rural livelihoods by which pastoralists are able to fully utilize untapped rangeland resources in distant areas. Household heads further explained their past experiences that livestock mobility has been used to escape away during a disease breakout in a specific area.…”
Section: Effects Of Adaptation Actions On Income Of Householdssupporting
confidence: 51%
See 3 more Smart Citations
“…The results further reveal that households who keep moving their cattle herds to better pasture had achieved higher income than those who never moved. In congruence with this finding, Moritz et al (2009) indicated that livestock mobility is the innovative means of sustaining rural livelihoods by which pastoralists are able to fully utilize untapped rangeland resources in distant areas. Household heads further explained their past experiences that livestock mobility has been used to escape away during a disease breakout in a specific area.…”
Section: Effects Of Adaptation Actions On Income Of Householdssupporting
confidence: 51%
“…Options for adaptation include diversifying income, building formal and informal institutions, adjustments in livestock holdings and species, labour mobility and engagement in small irrigation schemes (Adger et al 2005;Berhanu et al 2007;Seo and Mendelsohn 2008;Moritz et al 2009;Crane et al 2011;Tsegaye et al 2013). However, little empirical knowledge is available to help understand the effects of alternative adaptation strategies on household incomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transhumance can be described as animal husbandry involving moving animals in ways that best exploit natural resources (SWAC/ OECD 2007;Adriansen 2008;Moritz et al 2009). This system is based on opportunistic and seasonal exploitation of natural resources (Scoones 1995;Marty et al 2006).…”
Section: Introductionmentioning
confidence: 99%